What do the stats tell us? Engaging elementary children in probabilistic reasoning based on data analysis. (24th July 2015) - Hourigan, Mairéad; Leavy, Aisling
Summary: As part of Japanese Lesson study research focusing on 'comparing and describing likelihoods', fifth grade elementary students used real‐world data in decision‐making. Sporting statistics facilitated opportunities for informal inference, where data were used to make and justify predictions.